1998
DOI: 10.1902/jop.1998.69.6.686
|View full text |Cite
|
Sign up to set email alerts
|

Immunization With Porphyromonas gingivalis Cysteine Protease: Effects on Experimental Gingivitis and Ligature‐Induced Periodontitis in Macaca fascicularis

Abstract: Targeting bacterial virulence factors such as proteases for immunization may hold the key to hmiting or preventing loss of attachment and alveolar bone in periodontal disease. This study examined the chnical, microbiological, and immunological responses following active immunization with a purified Porphyromonas gingivalis cysteine protease (porphypain‐2) in the nonhuman primate (Nhp) Macaca fascicularis. One group of Nhp was immunized with porphypain‐2 antigen while control Nhp received placebo injections. AU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 24 publications
4
69
0
Order By: Relevance
“…Interestingly, this antigen also elicited a potent IgG response, and the animals immunized with P. gingivalis CPS were protected from P. gingivalis-elicited oral bone loss. To date, several P. gingivalis vaccine candidates have been reported to prevent P. gingivaliselicited oral bone loss (8,9,13,18,19,22,28) while other P. gingivalis antigens, such as LPS, do not appear to provide protection from subsequent P. gingivalis infection (5). Unexpectedly, we observed that mice immunized with P. gingivalis CPS develop an IgG response that recognizes P. gingivalis whole organisms.…”
Section: Vol 71 2003 Notes 2285mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this antigen also elicited a potent IgG response, and the animals immunized with P. gingivalis CPS were protected from P. gingivalis-elicited oral bone loss. To date, several P. gingivalis vaccine candidates have been reported to prevent P. gingivaliselicited oral bone loss (8,9,13,18,19,22,28) while other P. gingivalis antigens, such as LPS, do not appear to provide protection from subsequent P. gingivalis infection (5). Unexpectedly, we observed that mice immunized with P. gingivalis CPS develop an IgG response that recognizes P. gingivalis whole organisms.…”
Section: Vol 71 2003 Notes 2285mentioning
confidence: 99%
“…Despite this, there are no vaccines in use for the prevention of adult periodontitis. Because P. gingivalis is a significant periodontal pathogen, investigators have assessed the potential of several P. gingivalis antigens to function as vaccine candidates, including killed whole P. gingivalis organisms and specific P. gingivalis antigens such as fimbriae, fimbrillin peptides, gingipains, hemagglutinins, and others (7,9,11,13,22,29,31). A conjugate vaccine consisting of P. gingivalis CPS and P. gingivalis fimbriae was shown to prevent P. gingivalis infection when a murine subcutaneous challenge model was used (6).…”
mentioning
confidence: 99%
“…Immunisation with cysteine proteases, purified from P. gingivalis against CP, may be important to the prevention from RA and its treatment (24). P. gingivalis is associated with the citrullination process and might participate in the loss of self-tolerance after the development of RA.…”
Section: Microorganisms In Chronic Periodontitis and Their Potential mentioning
confidence: 99%
“…Clinical attachment level (CAL) values were calculated from the pocket depth and recession measures. A gingival bleeding score, following determination of the pocket depth measure, was obtained (21)(22)(23).…”
Section: Animalsmentioning
confidence: 99%
“…Genital coinfections, such as genital herpes, gonorrhea, syphilis, and chlamydia, as well as yeast and bacterial vaginal infections, or host responses to these pathogens, create an inflammatory environment that favors HIV-1 infection and dissemination (18). Periodontal disease in the form of gingivitis represents a form of mucosal inflammation that is found in a significant proportion of the world population (19,20), and there is a well-established and reproducible nonhuman primate model of ligature-induced gingivitis (21)(22)(23). The study described here addresses the question of whether the induction of a common moderate inflammatory state of the gingival mucosa impacts oral SIV transmission and the induction of immune modulators in the rhesus macaque model.…”
mentioning
confidence: 99%